Предмет: Алгебра,
автор: Melony2
Решите данное уравнение.
Приложения:
![](https://files.topotvet.com/i/3be/3be2a2a23e522bd9374ae58be5ea6f8f.png)
Ответы
Автор ответа:
1
- x² + 6x - 8 = 0
d = b² - 4ac = 6² - 4 × ( -1 ) × ( -8 ) = 36 - 32 = 4
√d = √4 = 2
x₁ = ( -b + √d ) / 2a = ( -6 + 2 ) / -2 = -4 / -2 = 2
x₂ = ( -b - √d ) / 2a = ( -6 - 2 ) / -2 = -8 / -2 = 4
d = b² - 4ac = 6² - 4 × ( -1 ) × ( -8 ) = 36 - 32 = 4
√d = √4 = 2
x₁ = ( -b + √d ) / 2a = ( -6 + 2 ) / -2 = -4 / -2 = 2
x₂ = ( -b - √d ) / 2a = ( -6 - 2 ) / -2 = -8 / -2 = 4
Melony2:
А в дроби разве не (-6 + 2) / - 2?
Похожие вопросы
Предмет: Английский язык,
автор: yanakoval022
Предмет: Английский язык,
автор: Боняшечка
Предмет: Английский язык,
автор: Жека2125
Предмет: Русский язык,
автор: polina09883
Предмет: Биология,
автор: dlistova12